2016
DOI: 10.1007/s10787-016-0262-7
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of Nigella sativa Linn: Part 2 Recent advances

Abstract: The black cumin or Nigella sativa L. seeds have many acclaimed medicinal properties such as bronchodilatory, hypotensive, antibacterial, antifungal, analgesic, anti-inflammatory and immunopotentiating. This review article is an update on the previous article published on Nigella sativa L. in this journal in 1999. It covers the medicinal properties and chemical syntheses of the alkaloids isolated from the seeds of the herb.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(35 citation statements)
references
References 101 publications
0
35
0
Order By: Relevance
“… 2004a , 2004b ; Ali & Blunden 2003 ; Ahmad et al. 2013 ; Akram Khan & Afzal 2016 ). Different pharmacological effects have been identified for NS, such as immune stimulation (Salem 2005 ), anti-inflammatory properties (Chehl et al.…”
Section: Introductionmentioning
confidence: 99%
“… 2004a , 2004b ; Ali & Blunden 2003 ; Ahmad et al. 2013 ; Akram Khan & Afzal 2016 ). Different pharmacological effects have been identified for NS, such as immune stimulation (Salem 2005 ), anti-inflammatory properties (Chehl et al.…”
Section: Introductionmentioning
confidence: 99%
“…Chemically, NS contains 30% fixed oils (mainly fatty acids), 0.40–0.45% volatile oils, vitamins, amino acids, proteins, carbohydrates, alkaloids, saponins, crude fiber, and minerals. NS oil (NSO) is rich in polyunsaturated fatty acids (PUFA), phytosterols, TQ (up to 25% in volatile oil), carvacrol, t-anethole, sesquiterpenelongifolene, and 4 terpinol (Liu et al, 2011 ; Akram Khan and Afzal, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The seeds of this plant contain oil, protein, alkaloids such as ni–glycine and ni–glydine, and quinones such as thymoquinone, saponin, and volatile essence. [ 15 ] The pharmacologic and biologic effects of N. sativa and thymoquinone, as the components of N. sativa , include antioxidant, anti-ischemic, anti-inflammation, analgesic, antiepileptic, and anticough effects. [ 16 ] Studies carried out on N. sativa have indicated that it has antibacterial, anticonvulsant, and antioxidant properties, reduces blood glucose, and collects the free radicals.…”
Section: Introductionmentioning
confidence: 99%